Comparative Assessment of Facilities Provision in Public And Private Primary Schools in Irepodun Local Government of Kwara State - Ajayi, Olumuyiwa; Salma, Azeez Arisekola (Universitas Pendidikan Indonesia, 2021)
The study focused on comparative assessment of facilities provision in public and private primary schools in Irepodun Local government of Kwara state Descriptive survey research design was used for this study. population of this study comprises all private and public primary school teachers in Irepodun Local Government Area of Kwara State. The sample size comprised of 80 teachers in 16 schools selected by simple random sampling technique from the total population of primary school. From the study, it shows Facilities provided based on findings includes: headmaster/principals offices, classrooms, laboratory, playground (WA=2.56) There was significant difference in the facilities provided in primary schools in Irepodun Local Government Area of Kwara State based on school type 01 (P0.05) There was no significant difference in the facilities provided in primary schools in Irepodun Local Government Area of Kwara State based on school location. 55 (P0.05). It was therefore recommended that, the management of both public and private primary schools should endeavor to provide adequate classroom facilities to meet up school enrolment, School administrators should establish good relationship with communities and organization that can assist them in the provision of playground/sporting facilities to facilitate effective teaching and learning.